Criminal enforcement as a human right - Salazar, Alonso (2017)
The criminal procedure consists of a number of stages comprising: Initial investigation, intermediate, trial, and criminal enforcement. The problem focuses in that last of these stages, as it has been traditionally neglected. Thus, the trial stage is reached, in some cases with an appeal phase, but after that, everything is disregarded. The truth is that the criminal enforcement stage is probably one of the most delicate in the entire process, as it goes from the theoretical level of the application of Criminal Law to a practical level, to its reality along with the involvement of Penitentiary Law. The invisibility of this stage has caused, in many cases, unpunished violation of human rights.